Multicellular Features of Phytoplankton - Abada, Adi; Segev, Einat (Frontiers in Marine Science, 2018)
Microscopic marine phytoplankton drift freely in the ocean, harvesting sunlight through photosynthesis. These unicellular microorganisms account for half of the primary productivity on Earth and play pivotal roles in the biogeochemistry of our planet (Field et al., 1998). The major groups of microalgae that comprise the phytoplankton community are coccolithophores, diatoms and dinoflagellates. In present oceans, phytoplankton individuals and populations are forced to rapidly adjust, as key chemical and physical parameters defining marine habitats are changing globally. Here we propose that microalgal populations often display the characteristics of a multicellular-like community rather than a random collection of individuals. Evolution of multicellularity entails a continuum of events starting from single cells that go through aggregation or clonal divisions (Brunet and King, 2017). Phytoplankton may be an intermediate state between single cells and aggregates of physically attached cells that communicate and co-operate; perhaps an evolutionary snapshot toward multicellularity. In this opinion article, we journey through several studies conducted in two key phytoplankton groups, coccolithophores and diatoms, to demonstrate how observations in these studies could be interpreted in a multicellular context.